COMMUNITY STRUCTURE AND DIVERSITY OF BENTHIC MACROINVERTEBRATES IN ALAM KANDUNG WATERFALL TULUNGAGUNG REGENCY - Desi Kartikasari; Tutik Sri Wahyuni; Syaiful Amfri; Rafinda Herina Suci (Jurusan Pendidikan Biologi, Fakultas Ilmu Pendidikan, Universitas Timor, 2023)
This research aims to determine the profile of the community structure and diversity of benthic macroinvertebrates in Alam Kandung Waterfall. Sampling was carried out at six stations of ± 100 individuals or stations that use surber net and hand net. Data collection for each station includes the composition and density of each species which is used to calculate taxa richness, abundance, IVI (Important Value Index), and diversity index (H'). The results showed that 37 taxa from 11 classes were found and varied at each station. At the first station, the highest taxa were found with a total of 19 taxa, and the lowest taxa at the second station with 7 taxa. The highest abundance is known at the first station and the lowest at the sixth station. The IVI results show that the first and second stations are dominated by the type of Sulcospira testudinaria which is sensitive to pollutants, and the third station and fourth are dominated by Tarebia granifera and Vellidae. The fifth station was dominated by Corixidae, while Thiara scraba and Atyidae were found in all stations. The results of the diversity index show that the first and fourth are lightly polluted, the second station is moderately polluted and the rest are not polluted. It can be concluded that the quality of waterfalls in Alam Kandung is still in a good category, reflected by the diversity of taxa and the presence of riparian vegetation.